Outcomes of Adrenalectomy in Patients with Unilateral Primary Aldosteronism: A Review - Steichen, O.; Zinzindohoué, F.; Plouin, P.-F.; Amar, L. (Hormone and Metabolic Research, 2012)
Aldosterone hypersecretion in primary aldosteronism is unilateral (aldosterone producing adenoma and primary unilateral hyperplasia) or bilateral (idiopathic adrenal hyperplasia). Laparoscopic adrenalectomy is nowadays the preferred approach to treat patients with unilateral primary aldosteronism. We review the outcomes of this intervention in recently published series. Laparoscopic adrenalectomy has a morbidity of 5–14%, mortality below 1%, and a mean hospital stay around 3 days. It generally results in the normalization of aldosterone secretion and in a large decrease of blood pressure and antihypertensive medication, but normotension without treatment is only achieved in 42% of all cases. Normotension following adrenalectomy is more likely in young and lean women with recent low grade hypertension than in obese men with long-standing high grade hypertension or a family history of hypertension. However, individual prediction of the blood pressure outcome is not accurate and predictors of hypertension cure should not be used to select patients for surgery. Age, associated health conditions and preferences of the patient are more relevant to this end.
Keywords: hyperaldosteronism; adrenalectomy; minimally invasive surgical procedures; treatment outcome; prognosis; spironolactone